The Integration of Artificial Intelligence in Academic Learning Practices: A Comprehensive Approach - Gabriela Alina Anghel; Cristina Mihaela Zanfir; Florentina Lavinia Matei; Camelia Delia Voicu; Ramona Adina Neacșa (Education Sciences)
The integration of artificial intelligence (AI) in education has profoundly transformed the learning landscape, offering significant opportunities for personalized, flexible, and efficient educational practices. This study explores the impact of AI on academic learning, focusing on the perceptions and behaviors of students from Valahia University of Târgoviște, Romania (N = 250). By analyzing the students’ use of AI tools such as learning assistants and content generation systems, this research identifies the factors influencing the integration of AI into educational practices. Using a quantitative approach with a self-administered online questionnaire, this study tested hypotheses regarding the influences of age, field of study, and self-reported AI usage on students’ perceptions of its impact on academic performance, motivation, and the development of essential skills such as critical thinking and learning autonomy. Statistical analyses were conducted using SPSS V26, and Spearman’s correlation revealed significant relationships between AI competency and perceptions of academic performance (ρ = 0.261, p < 0.001), personalized learning (ρ = 0.196, p = 0.002), and motivation (ρ = 0.234, p < 0.001). The results highlight AI’s potential to revolutionize educational practices by providing personalized learning experiences, stimulating motivation, and promoting lifelong learning skills. This research deepens the understanding of AI’s role in higher education and its implications for future learning models, emphasizing its capacity to transform both students and educators.